Food and nutritional security in times of COVID-19: a literature review (Research, Society and Development, 2022)
This work analyzed the situation of Food and Nutrition Insecurity during the COVID-19 pandemic, comparing Brazil with other countries that have adopted similar measures to help the most vulnerable populations. It also analyzed the consumption of ultra-processed foods and also the nutritional implications that a poor diet can have on the health of those who consume them. Also, analyzed the impact of lack of food diversity in obtaining micronutrients. It was a literature review whose research base were SCIELO, PUBMED and VHL, in addition to legislation and studies relevant to the subject. The articles were analyzed based on the following criteria: empirical and observational studies, in addition to systematic reviews. Although several countries, including Brazil, have offered help to the vulnerable population, such measures were not enough to contain the increase in families living in a situation of food insecurity, which further aggravated the situation of countries whose level of food insecurity was already high.